Decomposing systemic risk: The roles of contagion and common exposures - Grzegorz Hałaj; Ruben Hipp (Bank of Canada, 2024)
We estimate a structural model derived from the balance sheet identity to evaluate the effects of contagion and common exposure on banks' capital, which varies endogenously as a function of assets and liabilities. Through a regression approach inspired by the literature on structural vector autoregression, we infer the interdependence of banks' financial conditions. In this model, contagion can occur through direct exposures, fire sales, and market-based sentiment, while common exposures result from portfolio overlaps. We apply this model to granular balance sheet and interbank exposure data of the Canadian banking market. First, we document that contagion varies over time, with the highest levels around the Great Financial Crisis (GFC) in 2008 and somewhat lower levels for the pandemic period. Second, we find that since the introduction of Basel III, the relative importance of risks has changed, hinting that sources of systemic risk have changed structurally. Our new framework complements traditional stress-testing exercises focused on single institutions by providing a holistic view of risk transmission.
Keywords: G21; C32; C51; L14; 330; Econometric and statistical methods; Economic models; Financial institutions; Financial stability